Respuesta del cultivo de maíz (Zea mays) a la aplicación de bioestimulantes a base de fitohormonas y prebióticos - Narváez Fajardo, Alexi Stalin (2022)
The use of biostimulants has shown a positive impact on current agriculture, especially for the production of short-cycle crops such as corn, one of the most cultivated grasses in the country. The present work was carried out on a farm in the Buena Fe canton, Los Ríos province, with the objective of evaluating the responses of the corn crop to the application